From Embryo to Adult Life: Differential Expression of Visual Opsins in the Flatfish Solea senegalensis Under Different Light Spectra and Photoperiods - Frau, Sara; Paullada-Salmerón, José A.; Paradiso, Isabella; Cowan, Mairi E.; Martín-Robles, Águeda J.; Muñoz-Cueto, José A. (Frontiers in Marine Science, 2022)
Visual photoreceptors in fish are usually adjusted to the light environment to ensure the highest efficiency and the best adaptation. In Senegalese sole, metamorphosis determines a migration from pelagic to benthic habitats, with marked differences in both light intensity and spectrum. Here, we analysed the ontogeny of six visual photopigments, including rod opsin (rh1), and short wavelength-sensitive (sws1 and sws2), medium wavelength-sensitive (rh2.3 and rh2.4) and long wavelength-sensitive (lws) cone opsins, in sole specimens maintained under light-dark cycles of white (LDW), blue (LDB), red (LDR) and continuous white (LL) lights by using RT-qPCR and in situ hybridisation. Most of the opsins displayed a similar developmental expression pattern in all tested conditions. However, lower transcripts were detected under LDR and LL compared to LDW and LDB. A significant increase in gene expression was detected before and after metamorphosis, reaching minimum transcript levels at hatching and during metamorphosis. Interestingly, green opsins (rh2.3 and rh2.4) displayed a significant increase only before metamorphosis, with their expression remaining low during and after metamorphosis. Rod opsin as well as short-, medium-, and long-wavelength sensitive cone opsins were detected in retinal photoreceptors of sole from pre-metamorphic to adult stages by in situ hybridisation. In adults, short-wavelength cone opsins (sws1, sws2) were found in single cones whereas medium- (rh2.4), and long-wavelength (lws) cone opsins were present in double cones. The results obtained by in situ hybridisation in the retina of developing sole, in terms of number of positive cells and/or intensity of the labelling, were consistent with the ontogenetic transcript patterns found by RT-qPCR, suggesting that most of the visual opsin expression detected in whole specimens could correspond to retinal expression. Taken together, our results pointed out that the ontogeny of Senegalese sole is accompanied by a remodelling in opsin gene expression being green-cone opsins the most abundant photopigments in pre-metamorphosis and rod opsin the dominant visual photopigment from the completion of metamorphosis onward. These results enlarge our knowledge on flatfish metamorphosis and ecology but also provide useful information to develop light protocols adapted to the different ontogenetic stages that could improve welfare and production in sole aquaculture.